2018
DOI: 10.1177/1078155218769367
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent progressive multifocal leukoencephalopathy and central nervous system infiltration by multiple myeloma: A case report

Abstract: Progressive multifocal leukoencephalopathy rarely occurs in patients with multiple myeloma. Intracranial central nervous system invasion is also an uncommon event in multiple myeloma, occurring in less than 1% of cases. We describe herein an exceptional case of coexisting progressive multifocal leukoencephalopathy and intraparenchymal central nervous system myeloma infiltration. A 73-year-old woman with relapsed multiple myeloma was treated with 15 cycles of lenalidomide and dexamethasone, but therapy had to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Multiple myeloma with CNS involvement develops via hematogenous dissemination of malignant cells or contiguous spread of the tumor, often associated with PCL and cranial plasmacytoma, respectively. 1,15 Although it has been suggested that invasion of the CNS is enabled by treatment of MM with immunomodulatory drugs (IMiD), with a report of an MM patient receiving lenalidomide prior to CNS-MM progression, 17 this is not robust evidence. Data for EMD in general suggest that escape from the BM is enabled by mutations to tumor suppressor genes such as TP53, oncogenes such as RAS, and altered expression of adhesion molecules, as outlined above.…”
Section: Causementioning
confidence: 99%
“…Multiple myeloma with CNS involvement develops via hematogenous dissemination of malignant cells or contiguous spread of the tumor, often associated with PCL and cranial plasmacytoma, respectively. 1,15 Although it has been suggested that invasion of the CNS is enabled by treatment of MM with immunomodulatory drugs (IMiD), with a report of an MM patient receiving lenalidomide prior to CNS-MM progression, 17 this is not robust evidence. Data for EMD in general suggest that escape from the BM is enabled by mutations to tumor suppressor genes such as TP53, oncogenes such as RAS, and altered expression of adhesion molecules, as outlined above.…”
Section: Causementioning
confidence: 99%
“…Although large cohorts of patients with PML in the setting of natalizumab have been described, 17,18 most of the literature on diverse etiologies of PML in recent decades has been limited to small case series and individual reports, which are subject to publication bias based on either unexpectedly favorable or unfavorable outcomes. 19,20 With the new promise of effective therapy for this devastating disease, understanding the diverse presentations of PML is increasingly important because early manifestations may be difficult to recognize but are most amenable to treatment. Here, we report the risk factors and outcomes in a cohort of patients diagnosed with PML and followed at 2 tertiary care hospitals in the United States over a 25-year period.…”
mentioning
confidence: 99%
“…Many patients receive immunomodulator therapy(ies), with responses often consolidated with an autologous SCT 17. Cases of PML following the use of lenalidomide, dexamethasone, cyclophosphamide and the newer proteasome inhibitor ixazomib have all been reported 18–21. These cases highlight the importance of monitoring for neurological signs and symptoms in patients on immunomodulating drugs with early consideration given to PML.…”
Section: Discussionmentioning
confidence: 99%